Kewarganegaraan dan Kesehatan: Partisipasi Warga dalam Penanganan Pandemi COVID-19 di Indonesia - Rachman, Fazli; Fitra, Ilham (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2020)
This article aims to parse and identify the participation of citizens in handling the coronavirus pandemic in Indonesia. This article tries to “unfold” an overview of the relationship between citizenship studies and health. This research was conducted by a qualitative approach and descriptive design. Collecting data were obtained by using observation, documents study, interview, and literature study technique that was held on during January until Mei 2020. The data obtained were then analyzed by an interactive model. The research result shows that citizen has a central rule for handling the spread of corona virus. Citizen participation for handling COVID-19 conducted by educating people about coronavirus and COVID-19, and preventive measures. Another participation form is direct philanthropy action. Citizen participation for handling COVID-19 in Indonesia. Categories Level of citizen participation in Indonesia is the degree of citizen power. Urgent to develop synergy between state and citizen to improve the highest standard, comprehensive, and sustainable health.